Analisa Kualitas Daya Listrik Pada Gardu Distribusi Universitas Khairun - Ramly Rasyid; Miftah Muhammad (Fakultas Teknik Universitas Khairun, 2021)
The large number of applications of nonlinear loads in the electric power system has made the system current very distorted with a very high percentage of current harmonic content, THD (total harmonic distortion) can damage the power factor compensation capacitor, making the system power factor worse, causing interference. to the telecommunication system, increase system losses, cause various kinds of damage to sensitive electrical equipment, all of which cause the use of electrical energy to be ineffective which results in poor power quality. In this study, the collection of data obtained was based on methods such as the following, namely the measurement method. This measurement method measures the harmonic voltages and currents caused by non-linear loads.